Ethnic favouritism in Kenyan education reconsidered: When a picture is worth more than a thousand regressions - Rebecca Simson; Elliott Green (London School of Economics and Political Science (LSE), Department of International Development, 2019)
Does the leader's ethnicity affect the regional distribution of basic services such as education in Africa? Several influential studies have argued in the affirmative, by using educational attainment levels to show that children who share the ethnicity of the president during their school-aged years gain more years of education. In this paper we revisit this empirical evidence and show that it rests on problematic assumptions. Using Kenya as a test case, we argue that there is no conclusive evidence of ethnic favouritism in primary and secondary education, but rather a marked process of educational convergence among the country's larger ethnic groups. This evidence matters, as it shapes how we understand the ethnic calculus of leaders.
Keywords: 330; Ethnic Favouritism; Kenya; Education; Ethnicity; Distributive Politics; Patronage